The effect of the characteristics of pregnant women and stress on the psychological well-being - Mariah Ulfah; Suryo Ediyono; Ita Apriliyani (International Journal of Health Science and Technology, 2021)
Introduction: Pregnancy affects physical and psychological changes. Especially during the Covid-19 period, there is a possibility of stress. The health problems of pregnant women that are not handled optimally are related to psychological problems, this will affect the success of the postpartum period, including during the breastfeeding process. Therefore, it is necessary to conduct research related to stress conditions in pregnant women which will affect the psychological well-being of pregnant women. Objective: to determine the characteristics of the mother and the stress of pregnant women affects psychological well-being. Method: observational analysis with a cross-sectional design. The research population of pregnant women in the antenatal class with a sample of 60 people with data collection techniques using systematic random sampling. The results showed: there was an effect of maternal characteristics (age, gestational age, parity) on psychological well-being. And there is the effect of stress on psychological well-being with a p value of 0.000.